Factors Influencing Buprenorphine Prescribing among Physicians in New York State. (19th December 2019) - Marino, Leslie A.; Campbell, Aimee N.; Nunes, Edward V.; Sederer, Lloyd I.; Dixon, Lisa B.
Abstract : Background . Increasing access to buprenorphine is an important strategy for curtailing the opioid epidemic. Research is needed to understand what facilitates prescribing among waivered physicians and how to increase the willingness and capacity to prescribe. This study describes prescribing patterns in a sample of buprenorphine-waivered physicians in New York (NY) in 2016 and examines factors influencing prescribing capacity among waivered providers. Methods . Surveys were mailed to a random sample of 300 physicians with DEA waivers to prescribe buprenorphine in NY which assessed demographics, practice characteristics, buprenorphine prescribing patterns, and barriers/facilitators to prescribing buprenorphine. Analyses include simple logistic regression to calculate the odds ratio, 95% confidence intervals, and p values, respectively, to examine differences in individual predictors among physicians that were actively prescribing buprenorphine and those that were not. Results . 91 physicians responded to the survey, and 65% indicated they were currently prescribing buprenorphine. The mean patient census among physicians waivered to prescribe to 30 patients was 9.6 (SD = 9.7, median = 5), and to 100 patients, it was 60.5 (SD = 38.9, median = 72.5). Common facilitators included access to psychosocial referrals and better reimbursement, while inadequate resources, lack of time, and prior authorizations were the most common barriers. Conclusions . In addition to increasing the number of waivered physicians, policy-makers should provide enhanced training and implementation support for waivered physicians to start prescribing and facilitate continued and expanded prescribing among those already doing so.